2017
DOI: 10.5312/wjo.v8.i6.441
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative blood management strategies for patients undergoing total knee replacement: Where do we stand now?

Abstract: Total knee replacement (TKR) is one of the most common surgeries over the last decade. Patients undergoing TKR are at high risk for postoperative anemia and furthermore for allogeneic blood transfusions (ABT). Complications associated with ABT including chills, rigor, fever, dyspnea, light-headedness should be early recognized in order to lead to a better prognosis. Therefore, perioperative blood management program should be adopted with main aim to reduce the risk of blood transfusion while maximizing hemoglo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
18

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 168 publications
1
53
0
18
Order By: Relevance
“…The technique is also possible to significantly reduce postoperative pain Perioperative bleeding remains a severe issue in TKA, causing swelling, anaemia, and elevated blood transfusion rate. (7) Several measures have been used to reduce the bleeding incidence, blood loss volume and blood transfusion rate, including controlled hypertension, tourniquets, intraoperative intravenous/intra-articular tranexamic acid (TXA), and the application of cryotherapy after TKA, using the bandaging technique after TKA (8). TXA is an antifibrinolytic medication.…”
Section: Introductionmentioning
confidence: 99%
“…The technique is also possible to significantly reduce postoperative pain Perioperative bleeding remains a severe issue in TKA, causing swelling, anaemia, and elevated blood transfusion rate. (7) Several measures have been used to reduce the bleeding incidence, blood loss volume and blood transfusion rate, including controlled hypertension, tourniquets, intraoperative intravenous/intra-articular tranexamic acid (TXA), and the application of cryotherapy after TKA, using the bandaging technique after TKA (8). TXA is an antifibrinolytic medication.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the three PBM pillars, many individual elements can be combined to optimise the management of patients. Articles describing which elements can or should be implemented are numerous (Spahn, 2010;WHO, 2010;Goodnough & Shander, 2012;Shander et al, 2012;Isbister, 2013;Shander et al, 2013;Vaglio et al, 2016;Fullenbach et al, 2017;Kozek-Langenecker et al, 2017;Munoz et al, 2017;Themistoklis et al, 2017;Vaglio et al, 2017). However, no information or recommendations are provided on how to implement these elements in practice.…”
Section: Patient Blood Management Pillarsmentioning
confidence: 99%
“…Autologous donation is associated with a > 1 g/dL drop in hemoglobin (Hgb), precipitating an iatrogenic anemia in many patients. 4 Not surprisingly, studies have shown that patients who choose to utilize autologous donation have an increased risk of all transfusions (autologous or allogenic). 5 It has also been reported that a considerable amount of preoperative donations is ultimately wasted.…”
Section: Autologous Blood Donationmentioning
confidence: 99%